Diagnosis of human T-cell lymphotropic virus type 1 (HTLV-1) and type 2 (HTLV-2) infection in at-risk populations: past, present and future - Caterino-de-Araújo, Adele (2009)
Brazil presents the major number of human T lymphotropic virus type 1 and type 2 (HTLV-1 and HTLV-2) infections worldwide, with more than 2.5 million infected individuals. In 1993, HTLV serology was considered mandatory in blood banks. HTLV-1 causes adult T-cell leukemia and mielopathy associated with HTLV-1/tropical spastic paraparesis, in addition to other diseases. HTLV-2 has been pointed as the cause of some neurological manifestations and to interfere in HIV/AIDS progression. Commercially available serological assays, which identify specific antibodies, lack in correctly diagnosing, mostly for HTLV-2 infection. Several screening and confirmatory testing algorithm for HTLV-1/2 infections have been proposed, but none of them showed 100% efficiency in diagnosing high-risk individuals. Remarkable number of sera has resulted in indeterminate Western blot, and this could be a consequence of the viruses isolates employed for the kits composition. It has been proposed the use of molecular assays as confirmatory test, but they have not been employed in routine yet. Since 1991, the Immunology Department of Instituto Adolfo Lutz has led to carrying out the serological and molecular studies on HTLV-1/2 infections, and presently it has a challenge for improving the laboratory diagnosis of HTLV-2.